Cervical cytology screening in young rural girls between the age of 16-20 years - SHANKER MISRA, JATA; Anand Narian Srivastava; SINGH, SHIVANI (International Journal of Clinical and Biomedical Research, 2022)
Abstract Background Since the marriages are performed at an early age in the villages of rural India, the young girls are exposed to the early sexual exposure and subsequent prolonged sexual activity. These factors are instrumental in the development of precancerous lesions of cervix in the young girls. Method Rural cervical cancer screening program is in progress in the villages of western Lucknow. Since May 2013 and till date, a total of 189 camps has been organized and cytology done in 2980 women. The 118 of 2980 were in the group of 16-20 year and cytological findings obtained in them have been analyzed in relation to different risk factors of cervix. Result The incidence of squamous intraepithelial lesions of cervix (SIL) was found to be 15.2% (18 cases) in the 118 girls of the study group. The SIL was seen in the 50% of the 2 girls examined at 16 and 17 years but was low in the girls between 18 to 20 years. The SIL rate was maximum with nulliparous (19.3%), pain in lower abdomen (26.3%) and hypertrophied cervix (100%). Majority of the young girls were nulliparous (infertile) while pain in lower abdomen was the most common symptom and hypertrophied cervix the only clinical lesion encountered in these 118 women. Conclusions The young girls in the rural population are at high risk of developing SIL as they are married at adolescent age and are subjected to early sexual exposure and subsequent prolonged sexual activity. The villagers should be taught about the ill effect of early marriage in the development of cervical cancer and should be counseled to avoid child marriage. Key words Adolescent girls, Cervical cancer in rural women, SIL, Nulliparous, Pain in lower abdomen.